A holistic view on implementing hospital autonomy reforms in developing countries: a systematic review. Issue Volume 33:Issue10(2018) (13th December 2018) - Ravaghi, Hamid; Foroughi, Zeynab; Nemati, Ali; Bélorgeot, Victoria D
Abstract: The excessive use of resources, inefficiency and poor service quality in public hospitals has led developing countries to create reforms in public hospital governance, including autonomization. Hospital autonomy refers to the delegation of administrative rights to the hospital management team. The purpose of the present research is to review different aspects of hospital autonomy reforms in developing countries, such as incentives, preparations, obstacles and facilitators to change prior to implementation, impacts on achieving Universal Health Coverage (UHC) goals, challenges, outcomes and implications for implementation. A systematic review of the evidence from developing countries was performed. The results showed that these countries have undertaken autonomy reforms in order to improve the efficiency, quality and accountability of their hospitals. Also, studies emphasized the role of the World Bank in facilitation and guidance, and identified bureaucratic culture and political instability as barriers to change for the implementation of hospital autonomy reform. Preparations were limited to two key areas, i.e. ensuring access to healthcare services and ensuring the implementation of these reforms. The main challenges were lack of infrastructure, poor planning and policymaking, poor programme control, limited decision rights, inappropriate incentives and weaknesses in the accountability system. The results indicated that these reforms had no discernible effect on quality, efficiency and other management indicators, while leading to an increase in hospital costs and out-of-pocket payments. Also, implementing these reforms affected the progress toward achieving UHC. Overall, the results showed that there are two factors in failed implementation of these hospital reforms in developing countries: (1) lack of a systematic and holistic view, and (2) incomplete or poor implementation of different aspects of these reforms.